Reformulating the Contract Formats of Islamic Financial Institutions in Indonesia toward Maqâshid al-Syarî’ah-Based Contracts - Deity Yuningsih; Muh. Sjaiful (Karsa: Journal of Social and Islamic Culture, 2016)
This research aims to reveal the legal facts regarding the substance of the contract clauses in Islamic financial institutions such as Islamic banking, shariah pawn-shop, and takâful (sharia insurance) which show the nuance of capitalistic con-tract clauses. Based on the purpose of this paper, the scope of this study is limited to the normative contracts in several Islamic financial institutions in order to ref-lect the purity of the sharia norms as well as to produce a format of sharia contract that puts forward maqâshid al-syarî’ah as the basic orientation. To sharpen the analysis framework, this study applies normative legal method with a con-ceptual approach. It is found that several contracts in Islamic financial insti-tutions use money as the object of the agreement (contract). Of course, if it goes uncontrolled, it could potentially trap other parties in the contracts into the prac-tice usury (ribâ). In conclusion, it is necessary to reformulate the contract format of the Islamic financial institutions in order to make it in line with the maqâshid al-syarî’ah  so that it could benefit the costumers of the sharia economy.Copyright (c) 2016 by KARSA. All right reserved DOI: 10.19105/karsa.v24i2.1031